Mothers’ Vegetable Consumption Behaviors and Preferences as Factors Limiting the Possibility of Increasing Vegetable Consumption in Children in a National Sample of Polish and Romanian Respondents - Groele, Barbara (Nutrients, 2019)
Increasing the insufficient intake of vegetables in children may be difficult, due to the influence of parents and at-home accessibility. The aim of this study was to analyze the association between self-reported vegetable consumption behaviors and preferences of mothers and the behaviors and preferences of their children, as declared by them. The nationally representative Polish (n = 1200) and Romanian (n = 1157) samples of mothers of children aged 3–10 were obtained using the random quota sampling method, and interviewed for their and their children’s general frequency of consumption and preferences of vegetables in years 2012–2014. A 24 h dietary recall of vegetable consumption was conducted for mothers and their children. Associations were observed for general number of servings consumed per day by mother–child pairs (p < 0.0001; R = 0.6522, R = 0.6573 for Polish and Romanian samples, respectively) and number of types indicated as preferred (p < 0.0001; R = 0.5418, R = 0.5433). The share of children consuming specific vegetables was 33.1–75.3% and 42.6–75.7% while their mothers also consumed, but 0.1–43.2% and 1.2–22.9% while their mothers did not. The share of children preferring specific vegetables was 16.7–74.1% and 15.2–100% when their mother shared the preference, but 1.3–46.9% and 0–38.3% when their mother did not. The mothers’ vegetable consumption behaviors and preferences may be a factor limiting the possibility of increasing vegetable consumption in their children.